The free spaces in domestic housing - de Freitas Nerbas, Patrícia (Universidad Nacional del Litoral, 2020)
In the Brazilian context, the open areas along the urban blocks remain residual spaces, with irregular and small geometries, configuring urban slices without continuity and connectivity. This scenario can be seen in the images of large urban centers and is repeated, even more permissively and negatively, in the domestic housing of low-income populations. In this context, the article seeks to awaken the dialogue on formal strategies for open spaces around social housing and the respective environmental qualities related to human health. The intention is to debate the spaces of intermediation between the buildings, the urban voids as continuity and connectivity strategies for the integration of networks of green areas and their benefits. Thus, it contributes to the debate on land use patterns in communities in situations of social vulnerability and the benefits of free spaces in cities, raising questions about design strategies for green areas in communities in situations of social vulnerability. Therefore, developing the building project synchronously with open spaces, considering its possible benefits, seems to be opportune for the residents' quality of life, in addition to contributing to the production of more sustainable and healthy cities.